The impact of an acute high polyphenol, high fiber meal with and without aerobic exercise on metabolism in middle‐aged and older adults: A pilot study - L. J. Ater; E. K. Plantz; T. D. Manning; J. D. Akers; E. S. Edwards; S. P. Kurti (Physiological Reports)
Abstract A high fat, high carbohydrate (HFHC) meal can induce adverse triglyceride (TRG), glucose, and metabolic load index (MLI; TRG + glucose) in middle‐aged and older adults. A bout of exercise (EX) or an acute meal may attenuate these postprandial responses. This study aimed to determine whether a high polyphenol, high fiber meal with and without EX could reduce postprandial TRG, glucose, and MLI in this population. In a randomized crossover design, 10 healthy adults (56.9 ± 6.9 years, 6F, 4M) completed four conditions: (1) traditional HFHC, (2) T‐HFHC + EX, (3) HFHC meal with polyphenols and fiber (P‐HFHC), (4) a P‐HFHC + EX. Each participant consumed 12 kcals/kg body mass. The P‐HFHC was made with plant‐based ingredients to match the macronutrient composition of the T‐HFHC. EX, performed 30 min post‐meal, expended 25% of kcals consumed. Blood TRG and glucose were measured for 6 h post‐meal, and MLI was calculated. There was a significant time*condition interaction for TRG (p = 0.038), glucose (p = 0.001), and MLI (p = 0.026). The P‐HFHC condition had lower TRGs at 4 and 5 h (p = 0.031, p = 0.050). These findings suggest that a minimally processed meal or EX may reduce CVD risk in middle‐aged and older adults.